Co-development of internalizing and externalizing behavior problems during early childhood among child welfare-involved children. (November 2017) - Yoon, Susan; Yoon, Dalhee; Wang, Xiafei; Tebben, Erin; Lee, Guijin; Pei, Fei
Abstract: Using parallel-process latent growth curve modeling, we examine developmental trajectories of internalizing and externalizing behavior problems and identify early risk factors for behavior problems among 329 child welfare-involved children followed from age 2 years to 5 years. Data are drawn from the National Survey of Child and Adolescent Well-Being II. On average, internalizing behavior problems remained stable, while externalizing behavior problems decreased over time. Higher initial levels of internalizing behavior problems were associated with higher initial levels of externalizing behavior problems. Rates of change also had positive cross-domain relationships. Child neglect, exposure to intimate partner violence (IPV), insecure caregiver-child attachment, and caregiver mental health problems were associated with higher initial levels of internalizing and externalizing behavior problems. Exposure to IPV, out-of-home care, and caregiver drug use predicted rates of change in behavior problems. Our findings highlight the importance of comprehensive assessment and treatment for co-occurring internalizing and externalizing behavior problems in young children involved in the child welfare system. Results also indicate the need for identifying and addressing early risk factors to prevent early onset and continued development of behavior problems in high-risk children. Highlights: Internalizing behavior problems remained stable over time during early childhood among child welfare-involved children Externalizing behavior problems significantly decreased over time Higher initial levels of internalizing behaviors were associated with higher initial levels of externalizing behaviors Rates of change had positive cross-domain relationships Identified risk factors included neglect, intimate partner violence, insecure attachment, and caregiver behavioral health problems